Phytochemical Screening, Pharmacognostic Evaluation and Biological Activity of Amaranthus spinosus L - Khanal, Dharma Prasad; Raut, B; Dangol, K S (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
Herbal medicines possess a great demand in both developed and developing countries as a source of primary health care owing to their attributes having wide biological and medicinal activities, high safety margins and lesser costs. People living in rural areas of Nepal depend largely in the herbal medicines for the treatment. The present study concerns with the study of pharmacognostic characteristics, phytochemical constituents and the biological activity of Amaranthus spinosus L. The hexane, chloroform, ethanolic and aqueous extract of its aerial parts were subjected to preliminary phytochemical analysis and detected saponin, carbohydrate, tannin, protein, glycoside, flavonoid and phenol as phytoconstituents. The transverse section of the stem and leaves showed characteristic vascular bundle tissues. All the extracts were used for testing the antimicrobial activity and brine shrimp lethality. No extract showed the antimicrobial activity and ethanolic extract showed LC50 value of 31.62 ppm. Hexane, chloroform and water extracts were less toxic with LC50 values 236.88 ppm,194.98 ppm and 320.71 ppm respectively.DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.11999Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015Page: 29-34